Visible light photocatalytic efficiency and corrosion resistance of Zn, Ni, and Cu-doped TiO2 coatings - Mona Khalaghi; Masoud Atapour; Mohamad Mohsen Momeni; Mohammad Reza Karampoor (Results in Chemistry)
Titanium dioxide (TiO2) thin films exhibit encouraging photocatalytic activity for the degradation of dyes, organic compounds, and biological contaminants. These thin films were obtained using the sol–gel method to prevent issues related to the leaching and separation of TiO2 powder. Therefore, this technique could be effective for treating large volumes of wastewater generated by the textile and refining finishing industries. Typically, these wastewater streams contain heavy metals, which can hinder the process of photodegradation. Transition metals often participate in this procedure, allowing them to adsorb onto the surface of the photocatalyst and modify its photocatalytic performance. Consequently, this study investigated the effects of doping TiO2 with copper, nickel, and zinc. The impact of doping TiO2 with Cu, Ni, and Zn was examined by considering the morphology, visible light response, corrosion and photocorrosion performance, and photocatalytic activity. Grazing incidence X-ray diffraction (GIXRD) results show that dopants are uniformly distributed in the form of oxide states. Morphology and wettability tests indicate that the addition of dopants into TiO2 thin films can develop compact structures with a lower crystallite size, improved surface area, and hydrophilic surfaces. The Cu, Ni, and Zn doping coatings show increased visible light absorption, with the band gap decreasing from 3.05 to 2.3, 2.8, and 2.85 eV, respectively. The maximum photocurrent density is observed for a Zn-doped TiO2 photoelectrode, which facilitates greater light energy utilization for photocatalytic performance. Corrosion measurements under dark and light conditions for doped TiO2 coatings exhibited contrasting activities, suggesting high electrical conductivity under light illumination.